Morphological and molecular analysis of Western Pacific crown-of-thorns starfish Acanthaster cf. solaris (Schreber, 1793) in Southern Negros Island, the Philippines - Labnao, Aiken Nikko P.; Sienes, Persie Mark Q.; Palomar-Abesamis, Nadia (2024)
The crown-of-thorns starfish (COTS) is known to destroy coral reefs by ingesting scleractinian corals during population outbreaks. Previous studies showed that Acanthaster planci is comprised of four species collectively called the A. planci species complex. Despite available online database sequences, the Pacific group of COTS – known as either Acanthaster solaris or Acanthaster cf. solaris – lacks comprehensive morphological descriptions and museum voucher specimens. Hence, this study aimed to characterize COTS specimens from two sites located in southern Negros Island using morphological features and partial CO1 mitochondrial gene. Morphological and morphometric data were obtained for size, color, rigidity, pedicellariae, adambulacral and abactinal spines, and arms. Tube feet were collected for DNA barcoding. Genetic divergence was determined between southern Negros Island and reference sequences of the A. planci species complex using the Kimura 2-parameter substitution model. Specimens from SNI have a grayish-blue aboral body color with blackish-red spots distributed throughout the central disc. The body color turns grayish-white, and the spots become redder when the animals are exposed to air. They have six types of spines and minute pedicellariae all over the body. All the COTS individuals collected from southern Negros Island claded with the Pacific group of the species complex, labeled as Acanthaster cf. solaris. The intra-specific genetic divergence between southern Negros Island sequences and the Pacific clade was 0.192 and 0.38%, respectively. Our results validate the presence of A. cf. solaris in the Philippines and provide a more comprehensive morphological description of the species from the Indo-Pacific region. Voucher specimens of the species were deposited at the Silliman University Rodolfo B. Gonzales Museum of Natural History.